Safety and efficacy analysis of the off-label use of pipeline embolization devices for intracranial aneurysms: a propensity score matching study - Ma, Yajing; Deng, Xin; Chen, Zhen; Yuan, Yongjie; Guan, Sheng; Guo, Xinbin (Frontiers in Neurology, 2024)
Backgroud and objective: The safety and efficacy of on-label use of pipeline embolization devices (PEDs) is well established, however there is much controversy over its off-label use. This study aimed to investigate the safety and efficacy of the off-label use of PEDs for treating intracranial aneurysms.Methods: This single-center study retrospectively included patients with digital subtraction angiography-, computed tomographic angiography-, or magnetic resonance angiography-confirmed intracranial aneurysms treated with PEDs who were admitted to our institution between January 1, 2018, and July 1, 2022. Patients were divided into on-and off-label groups according to the Food and Drug Administration criteria published in 2021. Propensity score matching (PSM) was used to balance disparities in baseline information between the two groups. Safety outcomes included postoperative mortality and complication rates, whereas effectiveness outcomes included aneurysm occlusion rate (O'Kelly-Marotta grading system C + D grades), retreatment rate within 12 months, and postoperative functional score (modified Rankin scale [mRS] score). The study was approved by the Ethics Committee of Scientific Research and Clinical Trail of the First Affiliated Hospital of Zhengzhou University. Ethics number: KY 2018-098-02. All patients provided informed consent. Results: A total of 242 patients with 261 aneurysms (160 on-label and 101 off-label aneurysms) were included in this study. PSM yielded 81 pairs of patients matched for baseline information. Postoperative hemorrhagic, ischemic, and procedure-related complication rates did not reach statistical significance. In addition, no statistically significant differences in the aneurysm occlusion rate, retreatment rate within 12 months, postoperative functional score (mRS score), or mRS score deterioration rate was observed between the two groups. A higher incidence of in-stent stenosis was observed in the off-label (4.9% vs. 21%, p=0.002) groups than in the on-label group; however, all patients were asymptomatic.